Pilot study of a digital literacy-based intervention to confront concomitant crises amongst key food system actors in Chile - Kanter, Rebecca; Boza, Sofía; Acuña-Salazar, Paula (Frontiers in Sustainable Food Systems, 2023)
Introduction The fragility of food systems in Chile has been exposed through concomitant crises, from a social crisis in 2019 to the COVID-19 pandemic, and ongoing climate change. There is an increased dependence on information and communication technologies (ICTs) to produce, sell, and consume food and the digital divide has increased. The lack of digital literacy in Chile has not been evaluated or considered within comprehensive interventions. Methods To examine how local food systems can be strengthened, we conducted a pilot study of a digital literacy-based intervention with smallholder farmers, vendors, and consumers (n = 96) of different age groups (25–45 y, and 46–65 y) from adjacent urban and rural regions in Chile. Telephone surveys were carried out on the use of ICTs, access to the food environment, and agricultural practices during crises. A 5-week digital literacy intervention was carried out on digital confidence, the use of ICTs to generate networks, networks, the use of apps to sell or buy food, banking operations, and communication with state agencies. We also planned a virtual conversation about the food system and nutrition in Chile. Results All participants knew how to read and send WhatsApp messages but >50% of farmers and vendors reported cell signal problems. Between the 2019 social crisis and the COVID-19 pandemic, supermarkets as the main source of food decreased from 79 to 57%, and delivery increased from 2 to 17%. In total, 92% of the participants received the intervention, and 52% expressed satisfaction. Across participants, the average implementation score was 61%. Only one person connected to the virtual conversation. Discussion Crises have impacted how the Chilean population in both urban and rural regions navigate their food environment for their household as well as small-scale agricultural production in these areas; elucidating a greater dependency on ICTs amongst small-scale farmers, vendors, and consumers in Chile to buy and/or sell food. We also conclude that it is feasible to implement a digital literacy intervention for key food system actors in urban and rural settings in Chile. Future studies will contribute to the evidence base about the feasibility and impact of similar digital literacy interventions; an area of increasing importance given the rising prevalence of the digital food environment worldwide.